Space–time labeling diversity for distributed Goppa-coded cooperative networks over Nakagami-q channels - Chen, Chen; Yang, Fengfan; Xu, Hongjun (Physical communication, 2024)
This paper proposes the novel space–time labeling diversity for the distributed Goppa-coded cooperation (STLD-DGCC) scheme over the Nakagami-q fading channel to improve the performance of the short-to-medium information block transmission. Two different Goppa codes with the same information length are deployed in the source and the relay, respectively, with the Goppa code at the relay providing additional redundancy. Meanwhile, two distinct labeling mappers of M-ary quadrature amplitude modulation (M-QAM) are used in the novel space–time labeling diversity (STLD) to achieve the extra diversity gain and decrease the error floor (EF) region in the Goppa coding scheme. To lower the computational complexity of the maximum likelihood (ML) detection, a near-ML reduced-complexity (RC) detection approach that compromises the system performance and the computation complexity is proposed. In addition, two novel joint decoding algorithms based on the critical signal-to-noise ratio (SNR) threshold are presented at the destination, namely the parallel algorithm and serial algorithm, to enhance the overall performance of the proposed STLD-DGCC scheme. In the case of the Nakagami-q fading model, the analytical union bound of the average bit error probability is provided, which tightly matches the Monte Carlo simulated results at high SNR. The simulation results further indicate that the proposed STLD-DGCC scheme significantly outperforms both the corresponding non-cooperative Goppa coding scheme and the DGCC scheme without the STLD technique under identical conditions. Furthermore, the performance of the STLD-DGCC scheme surpasses that of the existing transmission scheme, offering a promising candidate for further small information block communications.